Nematodes and weeds control effects of Pueraria phaseoloides and Flemingia macrophylla fallows on establishment, survival and yield of plantain - Banful, B.; Hauser, S.; Ofori, K.; Kumaga, F. (African Journals Online, 2008)
The yield of plantain (Musa spp., AAB Simmonds) declines sharply after 1–2 years of cropping in West and Central Africa, due mainly to weeds and nematodes. A trial was carried out from January 2002 to October 2005 under two land-use systems (LUS) comprising 4–5 year-old bush fallow, dominated by Chromolaena odorata (L.) R. M. King & H. Rob, and a 20 year-old secondary forest, in three villages in southern Cameroon, to assess the effectiveness of Pueraria phaseoloides and Flemingia macrophylla as planted fallows for weed suppression and reduction in nematode damage of the plantain root system, and determine the yield response of different plantain sucker types to the weed suppression and reduced nematode damage. In each LUS, the treatments were a factorial combination of three levels of fallow system and four levels of plantain sucker type arranged in a randomised complete block design. Total above-ground biomass production of P. phaseoloides was 7.45 Mg ha-1, 4.2 times higher than F. macrophylla (1.78 Mg ha-1; P < 0.05). The high biomass of P. phaseoloides resulted in a significantly greater reduction in total weed biomass compared to F. macrophylla in both wet and dry seasons. Comparing the planted fallows, a sustained reduction in soil nematodes population was only under P. phaseoloides. Plantain Establishment and survival rates were of decreasing order: PIF (nursery)-derived “Essong” > Boiling water-treated “Essong” > Untreated “Essong”. P. phaseoloides produced significantly (P < 0.05) the highest plantain yield. There were no differences between the natural regrowth and F. macrophylla for all the plantain yield parameters. Sanitizing suckers (boiling and nursery-derived) increased actual yield and quantity of edible bunches by 35% and 26%, respectively, compared to the untreated. It was concluded that P. phaseoloides had the greatest positive effect on the growth and yield of plantain.